2020
DOI: 10.1590/0034-761220200327
|View full text |Cite
|
Sign up to set email alerts
|

O medo da morte flexibiliza perdas e aproxima polos: consequências políticas da pandemia da COVID-19 no Brasil

Abstract: Resumo Desde sempre a humanidade se aflige com o fim da existência. Em algumas ocasiões, como a atual pandemia do novo coronavírus, percebemos sua presença mais de perto. Até que ponto o medo da morte pode alterar percepções e crenças dos indivíduos? É nesse contexto de incertezas e medos que decidimos investigar de que modo a sociedade brasileira vem avaliando seus governantes, sobretudo em relação à política de isolamento social. A pandemia da COVID-19 alterou os eixos da polarização política. De um lado, go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
6
0
5
Order By: Relevance
“…Second, a dense urban network that connects and influences municipalities through transportation, services, and business (26) was not fully interrupted during peaks in cases or deaths. Third, political alignment between governors and the president had a role in the timing and intensity of distancing measures (7), and polarization politicized the pandemic with consequences to adherence to control actions (27). Fourth, SARS-CoV-2 was circulating undetected in Brazil for >1 month (20), a result of the lack of well-structured genomic surveillance (28).…”
mentioning
confidence: 99%
“…Second, a dense urban network that connects and influences municipalities through transportation, services, and business (26) was not fully interrupted during peaks in cases or deaths. Third, political alignment between governors and the president had a role in the timing and intensity of distancing measures (7), and polarization politicized the pandemic with consequences to adherence to control actions (27). Fourth, SARS-CoV-2 was circulating undetected in Brazil for >1 month (20), a result of the lack of well-structured genomic surveillance (28).…”
mentioning
confidence: 99%
“…In the same study, a higher frequency of feelings of depression, sadness, anxiety, and lack of sleep was identified among women. In a study by Pereira et al 32 , the extent to which fear of death can alter individuals' perceptions and beliefs was analyzed, and the results suggested that, as individuals become aware of fatal victims among their acquaintances, their perceptions changed. As a result, some individuals became favorable to isolation and willing to practice this measure for longer periods.…”
Section: Resultsmentioning
confidence: 99%
“…O ano de 2020 foi marcado de maneira abrupta pela pandemia da Covid-19, doença causada pelo vírus SARS-CoV-2 (novo coronavírus). Em 11 de março de 2020, a Organização Mundial da Saúde (OMS) declarou a Covid-19 como uma pandemia, que afeta as pessoas de maneiras distintas, podendo levar a morte, em especial, de pessoas mais velhas ou que já apresentem outras comorbidades (CREPALDI, 2020;MEDEIROS;BERTHOLINI, 2020).…”
Section: Introductionunclassified